Antifeminism, Profeminism, and the Myth of White Men's Disadvantage. - Bridges, Tristan (Signs: Journal of Women in Culture & Society)
This article analyzes how members of antifeminist and profeminist men's groups discursively situate themselves as stigmatized by privilege. While the antifeminist men engage in symbolic disclosures that locate (white) men as the "real victims" of gender inequality, the profeminist men rely on strategies of disidentification to symbolically position themselves as somehow outside of the relations of gender and racial power and privilege they organize to oppose. Both of these power-evasive strategies sustain hybrid hegemonic masculinity while responding to a predicament that some young, white, heterosexual men encounter. Faced with their association with the increasing visibility of privilege and systems of socially structured advantage, they develop discourses that sustain a denial of their structural positions of power. Both groups' strategies work to secure and obscure their institutionalized power by projecting atavistic masculinity onto other, marginalized, and subordinated groups of men and performances of masculinity, rendering gender and racial subordination less visible.